Pengaruh Variasi Tekanan Dan Komposisi Bahan Terhadap Pembakaran Briket Kulit Kopi (Coffea Canephora) Banyuwangi - Huda, Soffanul; Rubiono, Gatut; Qiram, Ikhwanul (Virtual of Mechanical Engineering Article, 2018)
In this study, variations in pressure and adhesive were carried out, with variations in pressure of 4cm, 4.5cm, 5cm and variations of adhesives including two variations of sieve raw material 10gr, 20 gr, 30 gr, 40gr, and 100 gr, 110 gr, 120 gr, 130 gr. sieve raw material. After the research process, the briquette fire temperature test was carried out including the heating value of the briquettes, the cooking test of 500 ml of water on each briquette variation. To test the calorific value in each briquette variation, type K thermocouple measuring devices are used. From the results of the study, the best flame temperature was found in coarse filter coffee briquettes with 110 gr adhesive variation and briquette size 4.5 cm, reaching temperatures of 602ºc and testing 500 ml of water. the resulting water heat reaches 68.9ºc during 00.05.20. From the results of research coffee briquettes waste briquettes have a very high fire heat level